Analisis Penerapan Diversification Across Time: Tinjauan Terhadap Kisaran Keuntungan Individual Saham (Studi Komparatif Rata-rata Keuntungan Kisaran Harga Saham Teoritik dengan Kisaran Harga Saham Aktual Pada Saham Indek LQ 45 Periode 1 Feb 06-36 Jan 07) - Shinta Heru Satoto (Universitas Kristen Maranatha, 2008)
The purposes of this research are to investigate the used of diversification across time model on investor’s stocks ownership by compared the average return of theoritical stock price and the average return of actual stock price. This research used the different holding periods to show how effective the long of each holding period of the investor to have the stocks by their own. It also investigate how speed the changes of theoritical stock price range and the actual stock price range, and the differences between that two range. The result shows that the average return of theoritical stock price is wider than the average return of actual stock price. And the theoritical stock price range is changing faster than the actual stock price range. The differences of the theoritical and actual stock price range are happened on weekly, 4th weekly and 8th weekly holding period. While at 12th weekly holding period, it found there is no differences between that two range.